2017
DOI: 10.1051/0004-6361/201630163
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of superluminous supernova LSQ14mo and its interacting host galaxy system

Abstract: We present and analyse an extensive dataset of the superluminous supernova (SLSN) LSQ14mo (z = 0.256), consisting of a multicolour lightcurve from −30 d to +70 d in the rest-frame (relative to maximum light) and a series of six spectra from PESSTO covering −7 d to +50 d. This is among the densest spectroscopic coverage, and best-constrained rising lightcurve, for a fast-declining hydrogenpoor SLSN. The bolometric lightcurve can be reproduced with a millisecond magnetar model with ∼ 4 M ejecta mass, and the tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 132 publications
(213 reference statements)
2
45
0
Order By: Relevance
“…Rearrangement of gas in the galaxy, gas transfer, or the interaction causing metal-poor H i gas to be funneled into the galaxy could explain the occurrence of a SLSN Type I at low metallicity even in this solar-metallicity galaxy and indeed there is a small population of metal-poor stars present at the SLSN site. New SF activity due to interaction was also proposed for three other SLSN-I hosts (Cikota et al 2017;Chen et al 2017a).…”
Section: Discussionmentioning
confidence: 90%
“…Rearrangement of gas in the galaxy, gas transfer, or the interaction causing metal-poor H i gas to be funneled into the galaxy could explain the occurrence of a SLSN Type I at low metallicity even in this solar-metallicity galaxy and indeed there is a small population of metal-poor stars present at the SLSN site. New SF activity due to interaction was also proposed for three other SLSN-I hosts (Cikota et al 2017;Chen et al 2017a).…”
Section: Discussionmentioning
confidence: 90%
“…There are other examples of potentially merging systems hosting cosmic explosions, detected in absorption line profiles such as GRB 090323 (Savaglio et al 2012) and GRB 100219A (Thöne et al 2013), and in imaging of the hosts (GRB 051022;Castro-Tirado et al 2007;Rol et al 2007, and GRB060814;Perley et al 2013). Similarly, interacting systems have also been detected in the host systems of superluminous supernovae (Chen et al 2017;Perley et al 2016a). However, the detection of mergers in GRB and SN hosts could be coincidental, especially at high redshift where mergers are much more frequent (e.g.…”
Section: Grbs and Sne In Interacting Systemsmentioning
confidence: 99%
“…Thus the host and its bright neighbour appear to be a close analogue of the MW-SMC system. Chen et al (2017) found that the host of one SLSN, LSQ14mo, was in a likely interacting system with a projected separation of 15 kpc, and proposed that this could increase the likelihood of SLSNe by triggering vigorous star formation. The brightest and bluest pixels in our HST images, likely corresponding to the highest starformation rate, actually appear to be on the other side of the galaxy, though we cannot exclude comparable starformation at the position of SN 2015bn until the SLSN has completely faded.…”
Section: Galaxy Spectroscopymentioning
confidence: 99%